The Autocratic Parliament : Power and Legitimacy in Egypt, 1866-2011 - Weipert-Fenner, Irene (Book collections on Project MUSE., 2020)
"Weipert-Fenner has created a comprehensive study of Egypt's parliamentary history from 1866-2011, using a systematic empirical analysis, to explore and explain the public outcry that followed the December 2020 election"--